Knowledge flows, externalities and innovation networks. Issue 8 (3rd August 2017) - Quatraro, Francesco; Usai, Stefano
ABSTRACT: Knowledge flows, externalities and innovation networks. Regional Studies . This editorial introduces the articles addressing the multifaceted and composite phenomenon of knowledge flows and externalities within innovation networks. The papers offer a diversity of country contexts, as well as analytical approaches and methods. Starting with methods, they contain econometric analysis as well as social network analysis and combinations of the two. While most of the papers use econometric analysis, the level of analysis ranges from firm and individual level to aggregate analyses at the sectoral and regional level. Moreover, patents are the main starting point, but the proposed contributions show once more how different the approaches can be when using the same variables. The country context is diverse and includes data sources from US and European regions.